Trypsin cleavage sites are highly unlikely to occur in celiac-causing restricted epitopes. Issue 2 (2nd April 2020) - Herman, Rod A.; Song, Ping; Mirsky, Henry P.
ABSTRACT: To assess risk, the European Food Safety Authority requires that the amino-acid sequences of newly expressed proteins in genetically engineered (GE) crops should be searched for partial matches with 9-mer restricted epitopes known to cause celiac disease. None of the 26 known celiac-causing 9-mer epitopes contain an in-silico predicted trypsin cleavage site. The probability of this occurring by chance alone is 0.000056. Based on the absence of in-silico predicted trypsin cleavage sites within 9-mer epitopes known to cause celiac disease, it can be concluded with very high confidence that true celiac-causing epitopes are highly unlikely to contain in-silico predicted trypsin cleavage sites and that this criterion can reliably be used to exclude the risk that imperfect 9-mer peptide matches within newly expressed proteins from GE crops cause celiac disease.